Pengaruh Pengintegrasian Teknologi Media Kahoot Dalam Pembelajaran Pendidikan Agama Islam Di Sekolah Dasar - amandaeka yulistranti; Muhammad Dewa Zulkhi (UIN Sulthan Thaha Saifuddin Jambi, 2023)
The purpose of this study was to see the effect of integrating Kahoot Media on learning Islamic Religious Education. This type of research is a mix method. This study involved several variables as research categories, namely responses and results with a total sample of 25 students in class VI. Data analysis used descriptive statistics. Integration was carried out at Public Elementary School 146/I, Jambi City. seen in the response, and the results of the evaluation of learning for each variable from the response in integrating Kahoot media get very good results while the results of the evaluation of student learning are included in the good category.